Policy incentives for smallholder adoption of climate-smart agricultural practices - van Asseldonk, Marcel; Girvetz, Evan; Pamuk, Haki; Wattel, Cor; Ruben, Ruerd (Frontiers Media, 2023)
There is a large and growing literature on the potential use of policy instruments for stimulating the adoption of Climate-Smart Agriculture (CSA) practices amongst smallholders. The objective of this article is to review and understand how the array of potential policy incentives can serve as mechanisms for enhancing adoption and upscaling of potential CSA practices by small-scale farmers in low-income countries. The review follows a matrix approach capturing where specific CSA practices (rows) are supported by typical policy instruments (columns) for enhancing widespread adoption. We first identify six key CSA practices, namely water management, soil and nutrient management, crop tolerance to stress, agroforestry and intercropping, crop rotation and mixed systems, and pest and disease management. Then we discuss the impact of those typical policy instruments, namely market prices, taxes and subsidies, land rights, rural finance, training and information, and certification and labeling. The review finds that most studies on this subject have a rather narrow focus on functional properties of a specific policy instrument and a particular CSA practice, thereby ignoring substitution, complementary or conditional effects between policy measures and CSA practices. Consequently, previous studies identify few incentives, particularly effective on their own. Wider perspectives on impact pathways point to the importance of sequencing and scaling for enhancing farmers' CSA adoption. We therefore advocate for more integrated approaches that also consider indirect effects of policy instruments on CSA adoption and pursue their systematic anchoring through successful policies that enhance widespread adoption.